A Complex Case of Infective Endocarditis With Systemic Complications - Sharma, Anmol; Maskey, Arun; Koirala, Parash; Pathak, Sunil; Phuyal, Subash; Shrestha, Pratyush (Nepalese Heart Journal, 2024)
A 25-year-old female, with a known case of small perimembranous VSD who was started on empirical anti-tubercular drugs for suspected bilateral tubercular sacroiliitis for the last 1 month presented with persistent fever and increasing shortness of breath. Transthoracic echocardiography revealed concurrent infective endocarditis (IE) affecting the aortic and mitral valves, with small perimembranous ventricular septal defect (VSD), and severe aortic and mitral regurgitation. Repeated blood cultures did not show any growth. Empirical management with intravenous ceftriaxone and gentamicin was initiated. After completing 2 weeks of IV Gentamicin, the patient developed severe headache, vomiting, and transient loss of consciousness. MRI Head confirmed subarachnoid hemorrhage. Emergency External ventricular drain placement ameliorated intracranial pressure-related symptoms. Digital subtraction angiography identified a mycotic aneurysm at left MCA bifurcation as a complication of IE, which was successfully managed through endovascular coiling. Repeat MRI showed subsiding SAH with areas of ischemia, most probably related to cerebral vasospasm. Her blood cultures were still negative, hence shifted to Inj Vancomycin. After a few days, the patient developed a fever with a fall in GCS. Lumbar puncture confirmed bacterial meningitis, subsequently treated with intravenous meropenem. Cardiac CT was done which revealed a small perimembranous VSD along with a small ruptured Sinus of Valsalva draining in the right ventricle. After successful treatment of SAH and meningitis, the patient underwent dual valve replacement (aortic and mitral), VSD closure, and Ruptured sinus of Valsalva repair. Postoperative recovery was uneventful, and the patient was discharged on the fifth postoperative day.